2017
DOI: 10.1002/chem.201701912
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Two Ammonium and Triazolium Sites of Interaction in a Three‐Station [2]Rotaxane Molecular Shuttle

Abstract: This paper reports on the synthesis of a tri-stable [2]rotaxane molecular shuttle, in which the motion of the macrocycle is triggered by either selective protonation/deprotonation or specific carbamoylation/decarbamoylation of an alkylbenzylamine. The threaded axle is surrounded by a dibenzo[24]crown[8] (DB24C8) macrocycle and contains three sites of different binding affinities towards the macrocycle. An N-methyltriazolium moiety acts as a molecular station that has weak affinity for the DB24C8 macrocycle and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…[23] In arotaxane-based architecture, asymmetry can be included in both the axle and wheel components. The majority of twostationm olecular shuttles reporteds of ar is based on nonsymmetricala xles, [18,24,25] but in principle the direction of motion in ar otaxanec ould be dictated by the asymmetry of the wheel component ( Figure 1). [22,[26][27][28][29][30][31] In am inimalistic design like that showni nF igure 1a,o nw eakening the interaction between the axle and the ring the formation of two orientational isomers could be envisaged.…”
Section: Introductionmentioning
confidence: 99%
“…[23] In arotaxane-based architecture, asymmetry can be included in both the axle and wheel components. The majority of twostationm olecular shuttles reporteds of ar is based on nonsymmetricala xles, [18,24,25] but in principle the direction of motion in ar otaxanec ould be dictated by the asymmetry of the wheel component ( Figure 1). [22,[26][27][28][29][30][31] In am inimalistic design like that showni nF igure 1a,o nw eakening the interaction between the axle and the ring the formation of two orientational isomers could be envisaged.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, we had already shown that copper(I)‐loaded phenanthrolines of type [Cu(phenAr 2 )] + were able to catalyze cyclopropanations [5b] and click reactions. [2d] Equally, the exposed copper(I) ions in the dimer [FeCu 2 ( 1 ) 2 )] 4+ (State II) should be capable of capping bis‐ethynyl terminated pseudorotaxanes with bulky stoppers via a click [16] protocol to form [2]rotaxanes. No catalytic activity was expected for complex [Cu 2 ( 1 ) 2 ] 2+ since the encapsulated copper(I) ions should be unreactive.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a deshielding is observed for all the signals related to the nuclei placed around the Tz core, whereas the Tz aryl peak remains almost unaltered and the Tz methyl group becomes shielded by 0.88 ppm. 31 , 40 , 41 These changes suggest that in Rot + both rings have moved toward the central triazolium station, with neither of them overtaking it.…”
Section: Resultsmentioning
confidence: 99%